(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The migration base of migration in metaphor is not always complete and clear. For example, a golden head, a moving word golden, what exact word it replaces is unclear. Maybe “precious”, “smart”, “wise”, etc. But this is unclear. Each of the listed words has a sema proportional to gold. When an analogy is created subjectively, it will be difficult, if not impossible, to reconstruct the analogy to someone other than the creator. So, the similarity underlying a metaphor influences the nature of the metaphor. Accordingly, a metaphor is understandable when the comparison is open, incomprehensible when the comparison is created, and invisible when the comparison is lost. Metaphor is a very common phenomenon, but it cannot be said that its use by all lexical-semantic groups is one and the same. There are also certain patterns in the transfer of names: in different cases, different lexical-semantic groups (LSG) are designated for transfers. For example, animal names are more metaphors for human character (e.g. fox, mole, deer, etc.). Of course, it is necessary to define such groups. In this article, metaphorical movements in the Uzbek and Kyrgyz languages are divided into groups and subjected to lexico-semantic analysis.